1997
DOI: 10.1111/j.1432-1033.1997.00636.x
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Complexes of ADP and Phosphate Analogs on the Conformation of the Cys707‐Cys697 Region of Myosin Subfragment 1

Abstract: Recent crystallographic studies have suggested structural differences between the complexes of S1 ˙ Mg ˙ ADP with the phosphate analogs aluminium fluoride (AlF−4), vanadate (VO3‐4) and beryllium fluoride (BeFx) [Fisher, A. J., Smith, C. A., Thoden, J. B., Smith, R., Sutoh, K., Holden, H. M. & Rayment, I. (1995) Biochemistry 34, 8960–8972; Smith, R. & Rayment, I. (1996) Biochemistry 35, 5404–54171. In this work, chemical modifications, namely labeling of Cys707 (the reactive SH1 thiol) and Cys707 – Cys697 (SH1‐… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

10
40
0

Year Published

2000
2000
2014
2014

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 36 publications
(50 citation statements)
references
References 45 publications
10
40
0
Order By: Relevance
“…However, fast-reacting cysteines against DTNB per mole of S1 are largely oxidized (1.5 over 2, i.e., 75%) during treatments with SIN-1 producing 60% inhibition of S1 ATPase activities, and it has been shown that oxidation or chemical modification of the two highly reactive cysteines of S1, Cys 707 and Cys 697 , results in strong inhibition of the S1 ATPase activities (28,45,51,52). This point was confirmed by the tight correlation between the fractional decrease of the extent of labeling of Cys 707 with IAF and the fractional decrease of S1 ATPase activity after exposure to SIN-1 reported in this article, as ascertained by S1 Cys 707 titration with IAF under well-established experimental conditions (34,35,45). These cysteines are located in the catalytic domain of S1, very close to each other in the 3D structure of a domain that undergoes significant conformational changes during the catalytic cycle (53,54), and the DSC results reported in this article showed that SIN-1-treated S1 has a largely impaired ability to attain the conformation of the obligatory intermediate catalytic state S1‚Mg 2+ -ADP‚P i , which in nontreated S1 is induced upon incubation with Mg 2+ -ADP‚V 1 (31,32).…”
Section: Discussionsupporting
confidence: 79%
See 1 more Smart Citation
“…However, fast-reacting cysteines against DTNB per mole of S1 are largely oxidized (1.5 over 2, i.e., 75%) during treatments with SIN-1 producing 60% inhibition of S1 ATPase activities, and it has been shown that oxidation or chemical modification of the two highly reactive cysteines of S1, Cys 707 and Cys 697 , results in strong inhibition of the S1 ATPase activities (28,45,51,52). This point was confirmed by the tight correlation between the fractional decrease of the extent of labeling of Cys 707 with IAF and the fractional decrease of S1 ATPase activity after exposure to SIN-1 reported in this article, as ascertained by S1 Cys 707 titration with IAF under well-established experimental conditions (34,35,45). These cysteines are located in the catalytic domain of S1, very close to each other in the 3D structure of a domain that undergoes significant conformational changes during the catalytic cycle (53,54), and the DSC results reported in this article showed that SIN-1-treated S1 has a largely impaired ability to attain the conformation of the obligatory intermediate catalytic state S1‚Mg 2+ -ADP‚P i , which in nontreated S1 is induced upon incubation with Mg 2+ -ADP‚V 1 (31,32).…”
Section: Discussionsupporting
confidence: 79%
“…This is in good agreement with the conclusions reached on the basis of Ca 2+ -ATPase and K + /EDTA-ATPase activity measurements (see above). Because S1 can be selectively labeled by IAF at Cys 707 (34,35,45), its oxidation by SIN-1 can also be monitored by the parallel decrease of the extent of labeling of S1 by IAF under the standard experimental conditions indicated in Materials and Methods. The results shown in Figure 3B fully confirmed this point and also demonstrated a tight correlation between the fractional decrease of the extent of labeling of Cys 707 with IAF and the fractional decrease of the S1 K + /EDTA-ATPase activity.…”
Section: Inhibition Of S1 Atpase By Sin-1 and Synthetic Peroxynitritementioning
confidence: 99%
“…Supporting evidence lies in the fact that modification of the actin C-terminus by proteolysis, antibody binding and by mutagenesis can significantly impact actin polymerization properties [Johannes and Gallwitz, 1991;Crosbie et al, 1994;Orlova and Egelman, 1995;Phan et al 1997;Hegyi et al, 1998;Kim et al, 1998]. Attachment of fluorometric probes to different parts of the actin showed that polymerization per se and the binding of specific proteins to the actin filament at a distance from the probe site could affect probe behavior [Feng et al, 1997;Moens and dos Remedios, 1997;Wen et al, 2000;Bobkov et al, 2002Bobkov et al, , 2004Borovikov et al, 2004].…”
Section: Budding Yeast As An Expression System For Mutant Actinsmentioning
confidence: 99%
“…These interacting structural elements could constitute an allosteric system through which actin-binding proteins on the filament surface could affect filament formation and stability. For example, regulatory proteins such as Arp2/3 and formin which bind at or near K118 on the surface [Rouiller et al, 2008;Goley et al, 2010; Thompson et al, 2013] could initiate a set of allosteric conformational changes to the strand-strand interface or C-terminus known to be important in actin polymerization [Johannes and Gallwitz, 1991;Crosbie et al, 1994;Orlova and Egelman, 1995;Phan et al 1997;Hegyi et al, 1998; Kim et al, 1998a,b] affecting both filament formation and stability.They termed this helical element the pathogenic helix because disease-causing mutations cluster in it and the elements with which it interacts. R256H in a-smooth muscle actin causes TAAD.…”
mentioning
confidence: 99%
See 1 more Smart Citation